A mesoporous non-precious metal boride system: synthesis of mesoporous cobalt boride by strictly controlled chemical reduction. Issue 3 (6th December 2019) - Jiang, Bo; Song, Hui; Kang, Yunqing; Wang, Shengyao; Wang, Qi; Zhou, Xin; Kani, Kenya; Guo, Yanna; Ye, Jinhua; Li, Hexing; Sakka, Yoshio; Henzie, Joel; et al.
Abstract : Generating high surface area mesoporous transition metal boride is challenging but interesting because incorporation of boron atoms can generate lattice distortion to form amorphous metal boride which has unique properties in catalysis. Abstract : Generating high surface area mesoporous transition metal boride is interesting because the incorporation of boron atoms generates lattice distortions that lead to the formation of amorphous metal boride with unique properties in catalysis. Here we report the first synthesis of mesoporous cobalt boron amorphous alloy colloidal particles using a soft template-directed assembly approach. Dual reducing agents are used to precisely control the chemical reduction process of mesoporous cobalt boron nanospheres. The Earth-abundance of cobalt boride combined with the high surface area and mesoporous nanoarchitecture enables solar-energy efficient photothermal conversion of CO2 into CO compared to non-porous cobalt boron alloys and commercial cobalt catalysts.